The Role of Collaborative Work Culture in Enhancing Teacher Effectiveness in SMK Negeri 1 Pabelan - Hermawan, Dhanang; Aswan, Mukhamad Kholil (MultiTech Publisher, 2025)
This research aims to explore the role of collaborative work culture in enhancing teacher effectiveness in SMK Negeri 1 Pabelan and its subsequent impact on student outcomes. Utilizing a qualitative approach, the study employed in-depth interviews and focus group discussions with teachers and school leaders to understand the dynamics of collaboration within vocational education settings. The findings reveal that a collaborative work culture positively influences teacher effectiveness by fostering continuous professional development, enhancing teaching strategies, and improving student engagement. By integrating interdisciplinary collaboration and co-teaching, teachers were able to provide a more holistic and relevant educational experience, bridging the gap between theoretical knowledge and practical skills. Moreover, collaboration was found to reduce professional isolation, increase job satisfaction, and encourage innovation among teachers. The study highlights the significance of investing in collaborative practices to improve not only teacher performance but also overall educational outcomes, particularly in vocational education, where the goal is to prepare students for the workforce. The originality of this research lies in its focus on vocational education, where the integration of academic theory with practical application is crucial, and where collaboration can significantly impact career readiness. This study provides valuable insights for educators, administrators, and policymakers aiming to enhance teaching quality and student preparedness in vocational settings